REFRIGERATION AND AIR CONDITIONING (RAC) TECHNOLOGY: UNRAVELLING ITS STATUS AT WORK - Malabago, Nolasco K.; Ermac, Eugenio A. (European Scientific Journal, ESJ, 2015)
Being the frontline state university in Central Visayas, Cebu Technological University (CTU) adheres to the 16 theories of Tech-voc training to make the school a replica of the industry. This study determined the status of material resource in refrigeration and air conditioning technology at CTU systems. There were fifty-five (55) respondents randomly selected from different campuses of the university to elicit responses on availability, adequacy and usability of such resources. The material resources of the refrigeration and air conditioning (RAC) technology of CTU are insufficient. Further, it can be inferred that insufficiency is paralleled with the need to upgrade the non-serviceable resources due to obsolescence, propel to produce qualified 21st century technology graduates, who are technologically savvy and globally competitive. And it is strongly recommended that the top management may consider enough budget allocation, to buy new RAC technology sets of equipment, for instructional improvement to boost quality technical and vocational education.